# 5(2x - 10)/2 + 14 = 19

10x - 50/2 + 14 = 19

10x -25 + 14 = 19

I am stuck- help

## the way you typed it, the entire bracket is divided by 2.

5(2x - 10)/2 + 14 = 19

5(x - 5) + 14 = 19

5x - 25 = 19-14

5x = 5 + 25

5x = 30

x = 6

## No problem! Let's continue solving the equation step by step:

10x - 25 + 14 = 19

First, let's simplify the expression inside the parentheses:

10x - 25 + 14 becomes 10x - 11.

Now we have:

10x - 11 = 19

To solve for x, we need to isolate the variable on one side of the equation. In this case, let's move the constant term (-11) to the other side of the equation by adding 11 to both sides:

10x - 11 + 11 = 19 + 11

This simplifies to:

10x = 30

Finally, divide both sides of the equation by 10 to solve for x:

10x/10 = 30/10

The equation then becomes:

x = 3

Therefore, the solution to the equation is x = 3.

## To solve the equation 5(2x - 10)/2 + 14 = 19, you need to follow a step-by-step process. Let's break it down:

Step 1: Simplify the expression inside the parentheses.

Inside the parentheses, you have 2x - 10. To simplify, multiply 5 by each term inside the parentheses:

5 * 2x = 10x

5 * -10 = -50

So now the expression becomes (10x - 50)/2 + 14 = 19.

Step 2: Simplify the expression further.

Inside the parentheses, we have (10x - 50). Since it is divided by 2, we can simplify it by dividing each term by 2:

(10x)/2 = 5x

(-50)/2 = -25

Therefore, the expression now simplifies to 5x - 25 + 14 = 19.

Step 3: Combine like terms.

Next, combine the numerical constants (-25 and 14) to get -11:

5x - 11 = 19.

Step 4: Isolate the variable.

To isolate the variable, we need to get rid of the constant term on the left side of the equation. We can do this by adding 11 to both sides of the equation:

5x - 11 + 11 = 19 + 11

5x = 30.

Step 5: Solve for x.

To solve for x, divide both sides of the equation by 5:

(5x)/5 = 30/5

x = 6.

So, the solution to the equation is x = 6.